2019
DOI: 10.9734/jesbs/2019/v32i130160
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Social Inequality in Exposure to Bullying at School 1994-2018

Abstract: Aims: To examine social inequality in exposure to bullying at school among adolescents and changes in social inequality over time. We applied data from seven nationally representative school surveys in 1994, 1998, 2002, 2006, 2010, 2014 and 2018 in Denmark, the Health Behaviour in School-aged Children (HBSC) study. Methodology: The study population was 11-, 13- and 15-year-olds, response rate 87.9%, N=33,460 with comparable data about exposure to bullying and socioeconomic status. The analyses included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…In general, the finding of a decreasing frequency of bullying is in line with other national and international findings [ 26 , 30 , 31 ]. In recent years, however, a decrease was recorded not only for active bullying but also for victims of bullying [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the finding of a decreasing frequency of bullying is in line with other national and international findings [ 26 , 30 , 31 ]. In recent years, however, a decrease was recorded not only for active bullying but also for victims of bullying [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Recent years have seen a considerable drop in bullying both internationally and in Germany [ 26 , 30 , 31 ]. In studies from Germany, the number of girls and boys that report having bullied other children is decreasing [ 26 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, the prevalence of school bullying varies considerably. Although some studies have found a decreasing tendency in the prevalence of exposure to bullying, from 24.4% in 1994 to 4.9% in 2018 in a case from Denmark (Due et al, 2019), the phenomenon and its prevention still calls for more research.…”
Section: Prevalence Of School Bullying In Lithuania and Norwaymentioning
confidence: 99%
“…In terms of the macrosystem, it is possible to compare a number of socioeconomic factors that could create a favourable climate for school bullying or, conversely, minimise the probability of school bullying in Lithuania and Norway. A study on social inequality and exposure to school bullying, conducted by Due et al (2019), reveals that school bullying is most prevalent among pupils from lower socioeconomic groups. Moreover, a previous study, conducted by Due et al (2009), indicates that adolescents who attend schools and live in countries where socioeconomic differences are larger are at higher risk of being bullied.…”
Section: Lithuania and Norway Within A Macrosystem Contextmentioning
confidence: 99%
“…Overall, current studies have documented declining tendencies in bullying experiences (Cosma et al, 2020; Due et al, 2019; Jadambaa et al, 2019; Niproschke et al, 2016). Nevertheless, about every seventh student in Germany is involved (Fischer et al, 2020).…”
Section: Bullying In School and Cyberbullyingmentioning
confidence: 85%